Early Childhood Music Arts in Improving Children's Language Development in TK Citra Mandiri batang Kuis District - Hilda Zahra Lubis, Nadilla Barus, Mayang Sitorus, Risma Chintya (Education Achievement: Journal of Science and Research, 2023)
The art of music is one of the learning methods used in learning, namely opening the lesson, carrying out the learning theme, and closing the lesson in early childhood education, one of which is formal education, namely TK/RA. The art of music in early childhood can develop aspects Early childhood development, one of which is early childhood language development, in the results of research in kindergarten schools. Citra Mandiri, Batang Subdistrict, Paya Village, picture of the teacher's strategy in developing children's language with the art of music, namely using one of the learning methods through the singing method, with the method Children's singing can develop expressive (speaking) and receptive (listening or paying attention) to develop children's language. This research will discuss how the art of music improves children's language development in kindergarten schools Citra Mandiri kecamatan Batang Paya gambar.